Ocular surface immune transcriptome and tear cytokines in corneal infection patients - Alenezi, Heba; Parnell, Grant; Schibeci, Stephen; Ozkan, Jerome; Willcox, Mark; White, Andrew J. R.; Carnt, Nicole (Frontiers in Cellular and Infection Microbiology, 2024)
Background Microbial keratitis is one of the leading causes of blindness globally. An overactive immune response during an infection can exacerbate damage, causing corneal opacities and vision loss. This study aimed to identify the differentially expressed genes between corneal infection patients and healthy volunteers within the cornea and conjunctiva and elucidate the contributing pathways to these conditions’ pathogenesis. Moreover, it compared the corneal and conjunctival transcriptomes in corneal-infected patients to cytokine levels in tears. Methods Corneal and conjunctival swabs were collected from seven corneal infection patients and three healthy controls under topical anesthesia. RNA from seven corneal infection patients and three healthy volunteers were analyzed by RNA sequencing (RNA-Seq). Tear proteins were extracted from Schirmer strips via acetone precipitation from 38 cases of corneal infection and 14 healthy controls. The cytokines and chemokines IL-1β, IL-6, CXCL8 (IL-8), CX3CL1, IL-10, IL-12 (p70), IL-17A, and IL-23 were measured using an antibody bead assay. Results A total of 512 genes were found to be differentially expressed in infected corneas compared to healthy corneas, with 508 being upregulated and four downregulated (fold-change (FC) <−2 or > 2 and adjusted p <0.01). For the conjunctiva, 477 were upregulated, and 3 were downregulated (FC <−3 or ≥ 3 and adjusted p <0.01). There was a significant overlap in cornea and conjunctiva gene expression in patients with corneal infections. The genes were predominantly associated with immune response, regulation of angiogenesis, and apoptotic signaling pathways. The most highly upregulated gene was CXCL8 (which codes for IL-8 protein). In patients with corneal infections, the concentration of IL-8 protein in tears was relatively higher in patients compared to healthy controls but did not show statistical significance. Conclusions During corneal infection, many genes were upregulated, with most of them being associated with immune response, regulation of angiogenesis, and apoptotic signaling. The findings may facilitate the development of treatments for corneal infections that can dampen specific aspects of the immune response to reduce scarring and preserve sight.